PENGARUH KOMPENSASI, KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL GRIYA SANTRIAN - Diputra Y., I Nyoman Yoeka; Mujiati, Ni Wayan (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect of compensation, leadership and work environment simultaneously and partially on the performance of employees at Hotel Sanur Beach, as well as finding the variables dominant influence on employee performance. The design of this research study associative. Sampling using proportional random sampling method, amounting to 100 people. Collecting data using a Likert scale questionnaire. Data analysis technique used validity, relialibitas, normality test, heteroscedasticity, multicollinearity test and multiple linear regression. The results showed that the variables simultaneously leadership, compensation, work environment, a significant influence on employee performance. Partially leadership variable, variable compensation, and work environment variables have a significant effect on the performance of employees at Hotel Sanur Beach, Sanur. Leadership variables are variables that give dominant influence to employee performance at Hotel Sanur Beach, Sanur. Advice can be given to the head of Hotel Sanur Beach, Sanur in order to provide an example of the importance of working as a team.
Keywords: Compensation, Leadership, Work Environment, Performance